The Relationship Between Pregnant Women's Understanding Of Covid-19 Prevention Efforts And Anxiety Levels During The Pandemic At Paron Public Health Center, Ngawi Regency - Crishmawati, Berliana; Andi Surya (PROFESSIONAL HEALTH JOURNAL, 2025)
The Covid-19 pandemic, which began in early 2020, has spread globally, and adherence to health protocols is considered a crucial step in reducing virus transmission and associated anxiety. This study aims to analyze the relationship between pregnant women's understanding of Covid-19 preventive measures and their anxiety levels during the pandemic at Paron Health Center, Ngawi Regency. This research employed a correlational design with a cross-sectional approach. The study population consisted of 94 pregnant women at Paron Health Center, with a sample of 76 respondents selected through Simple Random Sampling. Data were collected using a questionnaire, and statistical analysis was performed using Somer's D test (? = 0.05). The results indicate that the majority of pregnant women have a good understanding of Covid-19 preventive measures (90.8%), and most experience mild anxiety (52.6%). Statistical analysis revealed a ?-value of 0.560, which is greater than ? = 0.05, indicating no significant relationship between the understanding of preventive measures and anxiety levels among pregnant women during the pandemic. In conclusion, while the understanding of Covid-19 prevention is good, pregnant women's anxiety is more influenced by concerns related to pregnancy, such as fetal health and pregnancy complications, rather than by knowledge of Covid-19 health protocols.